The Keynesian and Neo-Keynesian Theories of Economic Crises: Some Theoretical Aspects - Piperkov, Petar (Research Papers, 2024)
The Keynesian tradition dates back to J. M. Keynes and, according to it, economic crises are endogenous phenomena. The article reviews some aspects of this tradition in light of the understanding of fluctuations from market equilibrium. The object is the currents in the Keynesian theory, and the subject – their views on economic crises. The purpose of the article is to highlight certain contradictions between the ideas of J. M. Keynes and the subsequent Keynesian schools, due to the original ideas of Keynes, which subsequently fell out of the Keynesian tradition, but are essential for understanding the genealogy of crises. Scientific methods such as historical-logical analysis, comparative analysis and synthesis were used.
Keywords: Economic crises; J. M. Keynes; Fundamental uncertainty; Neo-keynesianism; Neoclassical synthesis